Electro‐mechanical properties of inkjet‐printed graphene oxide nanosheets. Issue 3 (17th November 2016) - Nikolaou, Ioannis; Hallil, Hamida; Conédéra, Véronique; Plano, Bernard; Tamarin, Ollivier; Lachaud, Jean‐Luc; Talaga, David; Bonhommeau, Sébastien; Dejous, Corinne; Rebière, Dominique
Abstract : This study deals with the deposition of graphene oxide (G‐O) thin films by inkjet printing method on Love wave devices, forming up G‐O nanosheets in between the inter‐digitated transducers (IDTs) of the device. Experimental results were compared with 3D finite element calculations. Enhanced properties were observed by amalgamating ultra‐thin G‐O films with SiO2 and lead to optimized guided surface acoustic wave propagation. The structural model of the G‐O films provided useful information regarding the Young and the Shear modulus of the device, which are found near 470 and 196 GPa, respectively. The resulting Maxwelian viscoelastic components of G‐O sheets were compared theoretically and experimentally to each other based on the providing losses on the Love wave devices through the scattering parameters (S‐parameters). Similarly, the theoretical and experimental resonance frequency data showed a very good agreement. This behavior is attributed to the different mechanisms, thus combining the viscoelastic and gravimetric effects of the G‐O on the Love wave devices. Finally, The G‐O film was characterized using colocalized AFM/Raman imaging in order to assess its roughness and chemical homogeneity.